2000
DOI: 10.1038/sj.onc.1203640
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an isoform of integrin-linked kinase (ILK) that is upregulated in HT-144 melanoma cells following TGF-β1 stimulation

Abstract: We have shown previously that integrin-linked kinase (ILK) is upregulated in human HT-144 melanoma cells following TGF-b1 stimulation. Using mRNA from TGFb1 stimulated HT-144 cells and reverse transcriptase polymerase chain reaction, we have isolated a cDNA encoding a protein highly homologous to ILK. Sequencing of the full-length 1359 base pair cDNA and polypeptide translation revealed that this protein, designated ILK-2, di ers from the known ILK (hereafter called ILK-1) by only four amino acids, while the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
(34 reference statements)
4
22
0
Order By: Relevance
“…A monoclonal antibody raised against a sequence in the carboxyl terminus of ILK that is 100% conserved between human ILK-1 and rat ILK, recognized a single 50-kDa band on Western blots of all tissues and cells examined. Thus, whereas it has been suggested that the expression of different ILK isoforms may be developmentally and spatially restricted (23,27), the reason for the discrepancy in the reported size for ILK is unclear at this time.…”
Section: Pbs Mutants Of Ilk Are Incapable Of Paxillin Binding and Of mentioning
confidence: 49%
See 1 more Smart Citation
“…A monoclonal antibody raised against a sequence in the carboxyl terminus of ILK that is 100% conserved between human ILK-1 and rat ILK, recognized a single 50-kDa band on Western blots of all tissues and cells examined. Thus, whereas it has been suggested that the expression of different ILK isoforms may be developmentally and spatially restricted (23,27), the reason for the discrepancy in the reported size for ILK is unclear at this time.…”
Section: Pbs Mutants Of Ilk Are Incapable Of Paxillin Binding and Of mentioning
confidence: 49%
“…ILK activity has been implicated in growth factor and Wnt signaling pathways (14,17,18), as well as in integrin-mediated cellular processes including regulation of cell adhesion (14), fibronectin matrix assembly (19), and cell adhesion-dependent cell cycle progression (20 -22). A second human ILK isoform (ILK-2) that is selectively up-regulated in metastatic melanoma cells has recently been described (23).…”
mentioning
confidence: 99%
“…24 However, neither blockade of TGF-␤ with neutralizing antibody nor blockade of intracellular TGF-␤ signaling with Smad7 transfection could block the upregulation of ILK in hypoxic ECs (data not shown). In a previous report by Melchior et al, 25,26 there were 2 isoforms of ILK, namely, ILK1 and ILK2, that could only be discriminated by BamHI cDNA restriction. ILK1, which has no TGF-␤ responsive element in its promoter site and is not restricted by BamHI, was found to have typical characteristics of a housekeeping gene.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ILK promotes oncogenic transformation [14,15] and promotes tumor invasion partially due to the inhibition of E-cadherin [16,17]. The transcription factor Snail has been shown to directly regulate expression of E-cadherin via the ILK pathway, as overexpression of ILK causes a stimulation of expression of Snail [13].…”
Section: Introductionmentioning
confidence: 98%